2016
DOI: 10.1016/j.envres.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid antagonists and thyroid indicators in U.S. pregnant women in the Vanguard Study of the National Children's Study

Abstract: The sodium iodide-symporter (NIS) mediates uptake of iodide into thyroid follicular cells. This key step in thyroid hormone synthesis is inhibited by perchlorate, thiocyanate (SCN) and nitrate (NO3) anions. When these exposures occur during pregnancy the resulting decreases in thyroid hormones may adversely affect neurodevelopment of the human fetus. Our objectives were to describe and examine the relationship of these anions to the serum thyroid indicators, thyroid stimulating hormone (TSH) and free thyroxine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…Previous studies examining association between perchlorate exposure and maternal thyroid function in pregnancy have shown inconsistent results (Table 4 ). Although some studies [ 6 8 , 12 ] found no association between UPC and maternal thyroid function, others have shown that UPC is associated with low maternal FT4 and/or high TSH [ 9 11 ]. Possible reasons for the discrepant results include diverse study populations, different iodine status, and variable gestational age at the time of perchlorate and thyroid function assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies examining association between perchlorate exposure and maternal thyroid function in pregnancy have shown inconsistent results (Table 4 ). Although some studies [ 6 8 , 12 ] found no association between UPC and maternal thyroid function, others have shown that UPC is associated with low maternal FT4 and/or high TSH [ 9 11 ]. Possible reasons for the discrepant results include diverse study populations, different iodine status, and variable gestational age at the time of perchlorate and thyroid function assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This could lead to health hazards that may be more pronounced in vulnerable populations, such as pregnant women. Several studies have examined the effect of perchlorate and thiocyanate exposure during pregnancy on maternal thyroid function, however these showed conflicting results, and the potential adverse impact of exposure remains controversial [ 6 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It seems, therefore, that the results obtained in this study cannot be unambiguously extrapolated to estimate the effect of perchlorate on the level of thyroid hormones in breastfed babies. Mortensen et al [114] investigated the effect of perchlorate, thiocyanate and nitrate on the plasma thyroid hormone concentration in women in the third trimester of pregnancy. The study group consisted of 359 women from various locations in the United States.…”
Section: Thyroid Function Studiesmentioning
confidence: 99%
“…Tobacco smoke presents another important goitrogenic exposure due to its thiocyanate content. As individuals are unlikely to be aware of ingestion of most environmental goitrogens, it may be useful to consider estimating exposure through the use of biomarkers [ 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%